Evaluation of perinatal factors affecting the intervention in preterm patent ductus arterious - Miyamura, Fumiya; Mizukami, Tomoko; Egashira, Tomoko; Takayanagi, Toshimitsu; Shichijo, Akinori; Egashira, Masakazu (Journal of Japan Society of Perinatal and Neonatal Medicine, 2020)
【Aim】To know the perinatal factors in involving the onset of intractable patent ductus arteriosus during NICU admission. 【Subjects and Methods】The study subjects were 179 VLBWI whose gestational age were under 30 weeks after gestation（27.5±2.2wks, 950±297grams）. They were divided into two groups whether PDA was complicated or not. Secondary, PDA（+）was divided into two groups whether surgical ligation was required or not. Clinical eight factors were compared between two group, and logistic regression analysis was done to detect the significant variables. 【Results】Total numbers of PDA（+）was 83 and PDA（-）was 96. Ligation（+）was 14 and Ligation（-）was 69. By multivariate analysis, gestational age（p=0.001, OR0.78, 95%C.I. 0.68-0.91）and antenatal steroid administration（p=0.012, OR0.40, 95%C.I. 0.20-0.82）was selected as a significant variable to symptomatic PDA occurrence. Gestational age（p=0.003, OR0.58, 95%C.I. 0.41-0.83）was selected as a significant and antenatal diclofenac sodium administration（p=0.074, OR5.12, 95%C.I. 0.86-30.7）was select as a possible variable to require surgical ligation. 【Conclusion】In addition to gestational age, antenatal administration of steroid and diclofenac sodium may affect the severity of premature patent ductus arteriosus.